PELATIHAN PEMBUATAN BROSS DENGAN BAHAN DASAR KAIN PERCA DESA CANGKRINGTURI KECAMATAN PRAMBON KABUPATEN SIDOARJO - Aristha Purwanthari (Jurnal Abadimas Adi Buana, 2017)
Cain perca handicrafts are Crafts that memperpadukan between traditional and contemporary art. Perca handicraft is a combination of two sheets of cloth center in charge with the warming batting material from silicone. The top layer of handicrafts perca can consist of a combination or one of the patch work or application. The three layers of shaped sandwhich sewn with tailoring machine or hand (Delujur).Use of fabrics perca can be various forms but this time the use of fabrics perca only focused on bross. Bross is bross to scarf, so the committee invited only PKK mothers and women representatives from each RT. For the purpose of this activity is aimed to provide skills to the community so that later can increase their creativity and productivity to the community besides that can increase the level of community economic Turi Cangkring village when the handicrafts perca cloth can be in comersil. In the era of MEA economic competition tight enough so the requirement of qualified Human Resources improvements to compete with other countries. All the people who follow the training quite enthusiastic so that the implementation of the training the alleged price running well enough and smoothly. For almost two hours the people have been able to create bross from cain perca. As a result most people who participate are able to create bross beautiful and beautiful. Saw it should be village governments provide mentor for people who want to serve in the world of business sales bross. So that the proceeds from the sale of bross additional will gesture can earn money for their families.